Myelodysplastic syndrome: a review from University Hospital, Kuala Lumpur - Ng, S.C.; Kuperan, P.; Bosco, J.; Menaka, N. (Stamford Publishing Pte Ltd / Singapore Medical Association, 1990)
Twenty patients with Myelodysplastic Syndrome (MDS) were diagnosed in University Hospital, Kuala Lumpur over a 5 year period. They were subclassified using the French American British (FAB) criteria. 90% of the patients were above 40 years old and the sex ratio was about equal. The predominant presenting symptom was anaemia and there was paucity of physical signs at presentation. Patients with 'aggressive' subtypes of MDS i.e. refractory anaemia with excess blasts (RAEB), refractory anaemia with excess blasts in transformation (RAEB(-)+) and chronic myelomonocytic leukaemia (CMML) had more frequent thrombocytopenia and neutropenia and their marrow pictures frequently had dysmegakaryopoiesis and dysgranulopoiesis as compared to more the "benign" subtypes i.e. refractory anaemia (RA) and refractory leukaemic anaemia with ringed sideroblasts (RARS). Four patients had leukaemic transformation and all of them came from the 'aggressive' subtypes. The current views on treatment of MDS are discussed.